Falls and Fall-Prevention in Older Persons: Geriatrics Meets Spaceflight! - Goswami, Nandu (Frontiers in Physiology, 2017)
This paper provides a general overview of key physiological consequences of microgravity experienced during spaceflight and of important parallels and connections to the physiology of the aging. Microgravity during spaceflight influences cardiovascular function, cerebral autoregulation, musculoskeletal and sensorimotor system performance. A great deal of research has been carried out to understand these influences and to provide countermeasures to reduce the observed negative consequences of microgravity on physiological function. Important and enlightening parallels can be drawn between deterioration of physiological function due to aging and negative consequences of microgravity. For example, head-down bedrest is used as a model to study effects of spaceflight deconditioning due to reduced gravity. As older persons spend up to 80% of their time in hospital bed-immobilized, the deconditioning effects of bedrest confinement on physiological functions and parallels with spaceflight deconditioning can be exploited to understand both variations of deconditioning. Deconditioning due to bed confinement during hospitalization is a major factor in physiological deconditioning, especially in older persons, and can contribute to a downward spiral of increasing frailty, orthostatic intolerance, falls and fall-related injury. As astronauts in space spend substantial amounts of time carrying out exercise training to counteract the microgravity-induced deconditioning and to counteract orthostatic intolerance on return to Earth, it is logical to suggest some of these interventions for bed-immobilzed persons. Parallels between deconditioning due to reduced gravitational stress in space and during bed confinement can provide an integration of knowledge and method that incorporates aspects such as (mal-) nutrition, muscle strength and function, cardiovascular (de-) conditioning and cardio-postural interactions.The impact of such integration can lead to insights and methods of value to both space medicine and Geriatrics (Geriatrics meets spaceflight). For health care delivery to our aging population, improved approaches for carrying out early re-mobilization in bed-confined older persons can have a major impact in reducing the morbidity and the mortality associated with bedrest and in the costs related to aging care.